Regresyon analizinde ROC eğrisi kestirimi ile model seçimi - Köksal, Burcu (My University, 2011)
Regresyon analizi ile elde edilen doğrusal ve doğrusal olmayan model kestirimleri için model etkinliklerinin değerlendirilmesinde yararlanılan çeşitli model seçme ölçütleri mevcuttur. Bu çalışmada, temelde doğrusal olmayan ancak bazı dönüşümlerle doğrusallaştırılabilen lojistik regresyon modelleri için sıklıkla kullanılan model seçme ölçütlerine seçenek olarak ROC eğrisi kestiriminin kullanılabilirliği incelenmiştir. Uygulama çalışmasında yeni araştırmalar aracılığıyla sürekli gelişim gösteren ve güncelliğini koruyan, tüm dünyada olduğu gibi Türkiye’de de önemi son yıllarda giderek artan bir konu olan mutluluk kavramı ele alınmıştır. Türkiye’de mutluluk algısını etkileyen sosyo-demografik unsurlar öznel ve nesnel gösterge ayrımında değerlendirilmiştir. Bu amaçla nesnel ve öznel göstergeler kullanılarak nesnel, öznel ve karma model kestirimleri elde edilmiştir. Farklı model seçme ölçütlerine göre yapılan değerlendirmede ROC eğrisi kestirimi, kestirilen modeller arasından en iyi ayırım gücüne sahip olan modelin belirlenmesinde en uygun seçim ölçütü olarak saptanmıştır. Mutlulukla ilgili mevcut çalışmalarda çoğunlukla nesnel göstergelerden yararlanıldığı görülmüştür. Mevcut çalışma sonuçları ile uygulama sonuçları birlikte ele alınırsa, kişisel algıya göre farklılık gösteren mutluluk kavramı değerlendirilirken algıya dayalı olan öznel göstergelerin de dikkate alınmasının yararlı olacağı söylenebilir. Lojistik Regresyon Analizi, Model Seçimi, ROC Eğrisi, Mutluluk.

There are several model selection criteria which are used in evaluating the efficiency of linear and nonlinear models that are obtained by regression analysis. In this study, the availability of the ROC curve estimation was examined as an alternative option to commonly used model selection criteria for the logistic regression models, which are essentially nonlinear but can be linearized with some transformations. The notion of the happiness, which is a continuously improving and keeping up-to-date subject whereby the new researches and has an increasing importance in all over the world as well as in Turkey, was discussed in the application study. The socio-demographic factors affecting the perception of happiness in Turkey were evaluated at the separation of the subjective and objective indicators. For this purpose, objective, subjective and mixed model estimations were derived from the objective and subjective indicators. Based on the evaluation which was made according to the different model selection criteria, the ROC curve estimation was determined as the most appropriate model selection criterion which specifies the model that has the best discrimination power among the other estimated models. Mostly objective indicators were employed in the existing studies that are related to the happiness. If the results of the application and existing studies taken together, it can be said that it is useful to consider the subjective indicators, which are based on the individual perception, in evaluating the notion of happiness which varies according to the perception. Logistic Regression Analysis, Model Selection, ROC Curve, Happiness.
Keywords: İstatistik; Regresyon Analizi